The Effect of Health Education Through Video on Reproductive Health Knowledge Among Female Adolescents at MTS Al Ulum, Medan Area District - Suhartini; Sari, Juita; Rezeki, Sri; Batubara , Zuniah Rahma (Cattleya Darmaya Fortuna, 2025)
Adolescents are a vulnerable age group to reproductive health issues due to a lack of knowledge and limited access to information. The aim of this study was to determine the effect of health education through video on reproductive health knowledge among female students at MTS Al Ulum, Medan Area Subdistrict, in 2025. This research is a quantitative study using a one-group pretest-posttest experimental design. The population consisted of 144 female students, with a sample of 60 students from grades VII and VIII selected using proportionate stratified random sampling. Data were collected using a knowledge questionnaire administered before and after the health education intervention via video. Data analysis was conducted using the Wilcoxon test because the data were not normally distributed. The results showed an increase in knowledge after the health education video was provided. The average pretest score was 6.37, which increased to 7.60 in the posttest. The Wilcoxon test showed a p-value of 0.000 (p < 0.05), indicating a significant effect of health education through video on improving reproductive health knowledge among female students. The conclusion of this study is that video-based health education is effective in increasing adolescent girls’ knowledge about reproductive health. It is recommended that health workers, especially in community health centers, provide more education to students, particularly on how to maintain reproductive health using educational video media.